Perbedaan Psychological Well-being pada Ibu Bekerja dan Ibu Rumah Tangga di Kota Malang - Nur Eva; Afifah Wahda Tyas Pramudita; Sri Andayani (Fakultas Psikologi Universitas Pancasila, 2021)
One individual who has a complex role in his life is a mother, both housewives and working mothers. Up to a certain point, a mother whose main role is as a housekeeper can switch or increase the role of being a working mother. Housewives and working mothers are expected to be able to carry out each role maximally that can provide benefits for themselves and others. This then leads to psychological well-being, which is something everyone wants to have, including women who have roles as housewives or working mothers in Malang. This study aims to determine the differences in psychological well-being of working mothers and housewives. The subjects used in this study were mothers who had the latest junior high school education. All subjects live in the city of Malang and total 60 people. The result of the difference test is Z=0.296 and a significance of 0.767 (p>0.05). This indicates that there is no significant difference in the level of the psychological well-being variable between working and non-working mothers.